Anion-exchange Experiment of Zr, Hf, and Th in HNO3 and Quantum Chemical Study on the Nitrate Complexes toward Chemical Research on Element 104, Rf. Issue 6 (19th September 2022) - Watanabe, Eisuke; Kasamatsu, Yoshitaka; Yokokita, Takuya; Hayami, Sho; Tonai, Katsuma; Ninomiya, Hidemi; Kondo, Narumi; Shigekawa, Yudai; Haba, Hiromitsu; Kitagawa, Yasutaka; Nakano, Masayoshi; Shinohara, Atsushi
ABSTRACT: Anion-exchange behavior of Zr, Hf, and Th in nitric acid was investigated to determine suitable experimental conditions for the experiment of element 104, rutherfordium (Rf) and to obtain comparative data for discussion of nitrate complexes of Rf. Anion-exchange reactions in a Adogen 464/HNO3 system was found to reach equilibrium within 60 s, suggesting that the reaction system is suitable for the experiment of 261 Rf having a half-life of 68 s. We also studied the electronic states of Zr, Hf, and Th nitrate complexes by quantum chemical calculations. The calculation results support the experimental results that Th 4+ forms stable anionic complexes such as [Th(NO3 )6 ] 2− with a large coordination number of 12, while Zr 4+ and Hf 4+ do not.